2022
DOI: 10.1021/acssensors.2c00658
|View full text |Cite
|
Sign up to set email alerts
|

N–p-Conductor Transition of Gas Sensing Behaviors in Mo2CTx MXene

Abstract: It is highly important to implement various semiconducting, such as n- or p-type, or conducting types of sensing behaviors to maximize the selectivity of gas sensors. To achieve this, researchers so far have utilized the n–p (or p–n) two-phase transition using doping techniques, where the addition of an extra transition phase provides the potential to greatly increase the sensing performance. Here, we report for the first time on an n–p-conductor three-phase transition of gas sensing behavior using Mo2CT x MX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…196 Furthermore, Choi et al demonstrated the n−p-conductor transition of gas sensing behaviors in Mo 2 C 2 T x MXene, in which the organic intercalants (such as TMA + ) and film thickness significantly influenced the sensing performance. 101 The TMA + intercalation on Mo 2 C 2 T x induced a transition from n-type sensing behavior to p-type, while thicker films displayed a conductor-type gas sensing behavior. This transition indicates that the presence of TMA (and likely other intercalants) improves accessibility to gas molecules, in addition to tuning the electronic properties of MXene sensors.…”
Section: ■ Mxene Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…196 Furthermore, Choi et al demonstrated the n−p-conductor transition of gas sensing behaviors in Mo 2 C 2 T x MXene, in which the organic intercalants (such as TMA + ) and film thickness significantly influenced the sensing performance. 101 The TMA + intercalation on Mo 2 C 2 T x induced a transition from n-type sensing behavior to p-type, while thicker films displayed a conductor-type gas sensing behavior. This transition indicates that the presence of TMA (and likely other intercalants) improves accessibility to gas molecules, in addition to tuning the electronic properties of MXene sensors.…”
Section: ■ Mxene Propertiesmentioning
confidence: 99%
“…99 Besides Ti-based MXenes, Mo-MXenes are more stable 100 and have a smaller number of surface termination (T x ), as Mo atoms provide fewer electrons to surface functional groups. 101 V-MXenes have multiple oxidation states but showed the lowest chemical stability in their delaminated form in the colloidal state. 102 However, recent efforts showed progress in the chemical stability of V 2 CT x through the ion exchange process coupled with flocculation.…”
Section: ■ Mxene Familymentioning
confidence: 99%
See 3 more Smart Citations